Ituglanis compactus, a new species of catfish (Siluriformes: Trichomycteridae) from the rio Jari drainage, lower Amazon, Brazil - Castro, Íthalo Da Silva; Wosiacki, Wolmar Benjamin (Zootaxa, 2017)
A new species of Ituglanis is described from rio Iratapuru, near the rio Jari, Amapá, Brazil. The new species is distinguished from all congeners by the reduced number of post-Weberian apparatus vertebrae (36 or 37); the low number of paired ribs (2); the low number of interopercular odontodes (12–15); the number of branchiostegal rays (7 or 8); the presence of elongated fontanel in parieto-supraoccipital; the pectoral-fin rays (i,5); head length (18.9–25.0); and the presence of pores supraorbital s1, infraorbitals i1 and i3 of the laterosensory system. The new taxon has a reduced body size and fully ossified skeleton, but does not display a large number of paedomorphic traits compared to congeners. Comments about taxonomy and intrageneric comparisons are made, and paedomorphic in Ituglanis is discussed. Thoughts about conservation of the new species are presented.